Aceclofenac in the treatment of diseases of the locomotor apparatus - E. V. Igolkina; N. V. Chichasova; G. R. Imametdinova (Современная ревматология)
The paper highlights data on the mechanisms of action and efficacy of aceclofenac in chronic inflammatory diseases of the joint and spine (rheumatoid arthritis, spondyloarthritis) and osteoarthritis (OA). It shows the comparable efficacy of aceclofenac and nonselective nonsteroidal anti-inflammatory drugs in different rheumatic diseases. Randomized controlled trials and meta-analyses have revealed the high gastrointestinal safety of aceclofenac, which is comparable with that of celecoxib, including the low risk of gastrointestinal bleeding. Since aceclofenac has no negative effect on the articular cartilage and has a good tolerability, it may be given to persons of any age, including long-term use, which does not affect the safety of treatment.